1982
DOI: 10.1016/0031-9384(82)90308-0
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of latent inhibition by electrical stimulation of hippocampus

Abstract: The effects of low-level hippocampal stimulation on the development of latent inhibition were investigated employing classical conditioning of the nictitating membrane response of rabbits. Four groups were given either (a) no preexposure of the to-be-CS, (b) preexposure, (c) preexposure overlapped by hippocampal stimulation or (d) preexposure overlapped by cortical stimulation, followed by 300 conditioning trials for each group. After conditioning, the hippocampal group was divided into two groups designated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The switching model is silent with respect to neural processes occurring in pre-exposure, except for postulating the involvement of the entorhinal cortex (possibly with its serotonergic innervation), which is presumed to encode the stimulus-no event contingency. However, findings suggesting that the hippocampus and BLA are involved also in the pre-exposure stage Allan 1980, 1982;Romano 1999;Schauz and Koch 2000), and more critically, that manipulations of these structures in pre-exposure can disrupt LI (Salafia and Allan 1982;Schauz and Koch 2000), are rather disturbing for the model. Thus, a question arises as to how a dysfunction of a structure can lead to disrupted LI when occurring in pre-exposure yet lead to persistent LI when occurring in both stages?…”
Section: Effects At Pre-exposurementioning
confidence: 87%
“…The switching model is silent with respect to neural processes occurring in pre-exposure, except for postulating the involvement of the entorhinal cortex (possibly with its serotonergic innervation), which is presumed to encode the stimulus-no event contingency. However, findings suggesting that the hippocampus and BLA are involved also in the pre-exposure stage Allan 1980, 1982;Romano 1999;Schauz and Koch 2000), and more critically, that manipulations of these structures in pre-exposure can disrupt LI (Salafia and Allan 1982;Schauz and Koch 2000), are rather disturbing for the model. Thus, a question arises as to how a dysfunction of a structure can lead to disrupted LI when occurring in pre-exposure yet lead to persistent LI when occurring in both stages?…”
Section: Effects At Pre-exposurementioning
confidence: 87%
“…Although no other investigations of LI with ibotenate hippocampal lesions have yet been published, 1 one other hippocampal manipulation has produced augmented LI. Salafia and Allan (1982) reported that low-level electrical stimulation of hippocampus in a nictitating membrane conditioning paradigm during preexposure to tone stimuli resulted in significantly enhanced LI. This manipulation involved trains of low-level 40-Hz electrical stimulation, which were initiated with the preexposed CS and continued for 300 ms after CS termination.…”
Section: Discussionmentioning
confidence: 99%
“…Latent inhibition (LI) is a well-studied phenomenon whereby nonreinforced preexposure to a conditioned stimulus (CS) retards later learning of a conditioned response (CR) to that CS. This retardation of learning has been reported in a variety of research paradigms, including learned taste aversion (Aguado, Symonds, & Hall, 1994;Purves, Bonardi, & Hall, 1995;Reilly, Harley, & Revusky, 1994), appetitive tone-food pairing (Honey & Good, 1993), conditioned emotional response, conditioned suppression (Clark, Feldon, & Rawlins, 1992;Grahame, Barnet, Gunther, & Miller, 1994;Hall & Minor, 1984;Yee, Feldon, & Rawlins, 1995), and aversive eyeblink conditioning (Salafia & Allan, 1980, 1982Solomon & Moore, 1975). In eyeblink conditioning, preexposure to the tone CS makes an animal require more trials to reach learning criteria and asymptotic responding than are required by control animals.…”
mentioning
confidence: 82%
“…The Experiment 1 findings are very similar to those reported previously using similar stimulus parameters (Robinson, Port, & Stillwell, 1993), and they may provide an explanation of why many previous eyeblink conditioning experiments successfully reported LI effects: The successful earlier LI studies and the present study used either a shock US or a relative intense airpuff US. Also, many studies used percentage of CRs or total numbers of CRs (i.e., measures of overall CR performance across trials) as the measure of LI (e.g., Salafia & Allan, 1980, 1982; Solomon, Brennan, & Moore, 1974; Solomon, Lohr, & Moore, 1974; Solomon & Moore, 1975) instead of (or in addition to) reporting trials to a conditioning criterion (i.e., a measure of rate of initial learning). Differences in asymptotic responding in these previous studies could result in overall differences in the percentage or number of CRs observed and thus could be reported as an LI effect.…”
Section: Methodsmentioning
confidence: 99%